Can training trunk musculature influence musculoskeletal pain and physical performance in military police officers?. Issue 2 (1st February 2022) - Grani, Gabriel; Rodacki, Cintia de Lourdes Nahhas; Lubas, Henrique; Resende, Elisangela Franciele; Hoinatski, Rodrigo; Sentone, Rafael Gomes; Orr, Robin; Paulo, Anderson Caetano
Abstract: To investigate the effect of a Trunk Training (TT) program on the general musculoskeletal pain (GMP) and physical performance of Military Police Officers. Twenty officers were divided into either control group (CG) or TT group (TTG). Both groups performed nine weeks of traditional physical training. However, the TTG had 25-minutes allocated to TT during each scheduled physical training period. Anthropometric, trunk endurance, and physical fitness tests were completed pre- and post-training for both groups. Both groups also answered a weekly questionnaire about their GMP. Post-training, trunk endurance performance was significantly higher ( p < 0.05) and the GMP significantly lower ( p < 0.05) in the TTG when compared to the CG. Improvement in side plank test scores was associated with a decreased in GMP ( r = −0.495, p < 0.05). TT can reduce the perception of GMP in addition to increasing the endurance of the trunk muscles. The side plank was the only physical test associated with GMP. Practitioner summary: Trunk Training can reduce general musculoskeletal pain and increase the endurance of the trunk muscles without a concomitant loss in general fitness in elite Military Police Officers. This research lasted 11 weeks and presents real-world and pragmatic findings.